DESCRIPTION OF HANAFISM IN THE SCIENTIFIC HERITAGE OF MAHMUD ZAMAKHSHARI - S. S. Saidjalolov (Scholars Digest Publishing, 2023)
Mahmoud Zamakhshari is a great commentator, mutakallim, jurist who grew up in Movarounnahr. At the time when the scientific, cultural and economic situation in Movarounnahr was in decline, Mahmoud Zamakhshari served to revive and restore science with selfless scientists. Ten of his works are known today, and scientific researches on these works continue without stopping.
Keywords: Fiqh, Zamakhshari, Abul-Husayn Ahmed ibn Ali Domghani, interpretation, fiqh, kalam, As-Sadid al-Khayati, Kashshof.